Electricigens: source, enrichment and limitations. Issue 1 (1st January 2017) - Yousaf, Sameen; Anam, Maira; Saeed, Samia; Ali, Naeem
ABSTRACT: Recent concerns to maximize the power output and achieve the scale-up applications of microbial fuel cell (MFC) technology demand the selection of enriched electroactive consortia from diverse natural habitats such as soil, sediments and wastewater. To further improve the MFC performance, a fundamental knowledge of microbiology of electrochemically active bacteria (EAB) is required. This review presents the various enrichment strategies, engineering and microbiological approaches to optimize the microbial communities with improved electrigenic potential that could be used to enhance the MFC performances. The development of functionally stable electrigenic and electrotrophic microbial communities on anodes and cathodes of MFCs could extend the scope of this technology beyond the bioelectricity generation and wastewater treatment to the electrosynthesis of higher value products and bioremediation. Moreover, investigating the effect of various exogenous factors and limitations on the enrichment of EAB could advance the commercial applications of MFCs.